An estimate of the number of tropical tree species - Slik, J.W.F.; Arroyo-Rodríguez, V.; Aiba, Shin-Ichiro; Álvarez Loayza, P.; Alvese, L.F.; Ashton, P.; Balvanera, Patricia; Bastian, Meredith L.; Bellingham, P.J.; Berg, E. van den; Bernacci, L.; Conceição Bispo, Polyanna da; et al. (National Academy of Sciences, 2015)
People are fascinated by the amazing diversity of tropical forests and will be surprised to learn that robust estimates of the number of tropical tree species are lacking. We show that there are at least 40,000, but possibly more than 53,000, tree species in the tropics, in contrast to only 124 across temperate Europe. Almost all tropical tree species are restricted to their respective continents, and the Indo-Pacific region appears to be as species-rich as tropical America, with each of these two regions being almost five times as rich in tree species as African tropical forests. Our study shows that most tree species are extremely rare, meaning that they may be under serious risk of extinction at current deforestation rates.